PENERAPAN FINGER PAINTING DALAM UPAYA MENINGKATKAN KETERAMPILAN MENULIS ANAK AUTIS - ROHMATUN NISAK, BISMI (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Autism children were one of the special need children who had several problems relating with the development so it influenced their education. In education world, children were hoped to be able to read, write, and count, whereas the autism children had hindrance in fine motoric which made the writing skill of autism children less good. It could be observed to the result of the children’s writing which had measurement too big and the letters form was not consistent that difficult to read. The purpose of this research was to prove that the writing skill of autism children could be enhanced through finger painting in education institution of ABK Insani Mandiri Sidoarjo. This research used quantitative approach with pre-experiment kind and pre-test and post-test in one group (one group pretest – posttest) with 6 autism children as the subject. The data analysis used statistic non parametric with Wilcoxon sign test. The research result indicated that there was enhancement of writing skill of autism children through the application of several techniques in finger painting suitable with the average result of pre-test i.e. 39,167 and the result of average value from post-test was 53,34. From the result of data analysis it could be concluded that the counting rate from Z = 2,20. The rate was then compared with critic value 5% Z table i.e. 1,96. It proved that the value of Z table > 1,96 which meant that Ho was refused and Ha was accepted. It meant that the writing skill of autism children in education institution of ABK Insani Mandiri Sidoarjo could be enhanced through the application of finger painting.   Keywords: finger painting, writing skill